A benthic habitat sensitivity analysis of Qatar's coastal zone. (June 2021) - Butler, Josh D.; Purkis, Lotte M.; Purkis, Sam J.; Yousif, Ruqaiya; Al-Shaikh, Ismail
Abstract: Characterizing benthic habitat sensitivities of rapidly-developing countries is of paramount importance. Recent efforts defining the benthic habitat of Qatar's coastal zone with a high-resolution, ground-truthed benthic habitat map has provided a framework on which to develop a habitat sensitivity map. Here we present a sensitivity analysis catered towards identifying habitats with varying sensitivities to natural and anthropogenic stressors on a quantitative scale from 1 to 5, low to high. We have identified that the majority of the coastal area is low risk habitat (i.e. sandflats). However, there are six areas which are assigned as high risk by virtue of their rich occurrences of seagrass meadows, mangrove forests, and coral reefs - [1]. The reefs offshore of Al Zubarah on the west coast of the peninsula; [2] The Al Ruwais fringing reef on the northern tip of the peninsula; [3] The east-coast bays of Al Khor and Al Dhakira; [4] The shore-attached reef complex off Mesaieed (east coast); [5] The Jazirat al Bushayriyah offshore high; and, [6] The entire shelf of Halul Island. The sensitivity analysis presented here builds on a recently-developed benthic habitat map of Qatar's coastal zone and covers a total are of 4500km 2 . Results gleaned from this analysis can be used to support marine spatial planning objectives and ecosystem-based management decision making.